Intra-union flexibility of non-ETS emission reduction obligations in the European Union - Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
The current EU proposal on greenhouse gas emission reduction has 28 targets for 2020: an EU-wide one for carbon dioxide emissions covered by the European Trading System, and one target for non-ETS emission per Member State. Implementation is necessarily more expensive than needed. I consider three alternative proposals to reduce costs. In the Irish proposal, Member States can purchase ETS permits to offset excess non-ETS emissions. In the Polish proposal, Member States can sell excess non-ETS emissions in the ETS. In the Swedish proposal, Member States can trade their non-ETS allocations. I compare these three alternatives to the default policy (no flexibility outside the ETS) and to the cost-effective solution (full flexibility). I calibrate a simple model to the results of the impact assessment of the European Commission. This reveals that European Commission did not fully disclose all details, and that odd assumptions were made. In the case of three Member States, the non-ETS allocation exceeds the projected emissions. The results show that the alternative flexibility mechanisms would be used to only a limited extent, but would help to suppress the costs of meeting the target. The Swedish and Polish proposals come closest to the cost-effective solution as full use is made of the hot air in the non-ETS system. The Irish proposal performs best if there are negative surprises in either the cost of non-ETS emission reduction or non-ETS emission projections.
Keywords: Q54; 330; climate change; emissions trade; European Union; Klimaveränderung; Treibhausgas; Emissionshandel; EU-Umweltpolitik; EU-Staaten